The economywide impacts of climate change on Philippine agriculture - Rosegrant, Mark W.; Perez, Nicostrato; Pradesha, Angga; Thomas, Timothy S. (International Food Policy Research Institute, 2016)
FOR MOST COUNTRIES, HIGH PRODUCTIVITY GROWTH IN THE AGRICULTURAL SECTOR HAS BEEN A KEY DRIVER of structural transformation promoting long-term economic growth. Historically, low agricultural productivity growth has hindered economic growth and employment creation in the Philippines, where agriculture—which accounts for one-third of employment—remains a key sector. Climate change has the potential to disrupt crop productivity, and in turn affect domestic agricultural production, consumption, and food security. Moreover, the global impact of climate change could stimulate changes in international and domestic commodity prices, ultimately having negative effects on both Philippine agriculture and the country’s overall economy. Developing agricultural adaptation and growth strategies is of utmost importance, not only to maintain domestic agricultural production, but also to underpin broader economic growth and structural transformation. Sustaining agricultural production growth to help achieve inclusive growth and poverty reduction is a key goal for the Philippine government.